Temporal drop of genetic diversity in Bombus pauloensis - Maebe, Kevin (2019)
Bumblebees are economically important insects which perform essential pollination tasks in natural and managed ecosystems. Recent research studying Neotropical bumblebee species in Brazil showed a clear decrease in genetic diversity over time in Bombus pauloensis. A new temporal assessment of genetic diversity is needed to know whether this was a location-specific result, or a more general phenomenon. This knowledge is essential to be able to prioritize conservation and management needs. Here, the genetic variability of B. pauloensis populations in Argentina was investigated over time using museum collection specimens from 1933 to 2016, and compared with reanalyzed data from Brazilian populations. Furthermore, specific time series were made for two Argentinean locations, Candelaria and La Plata, and compared with the time series of Porto Alegre (Brazil). All collected specimens were genotyped with 16 microsatellite loci to estimate genetic diversity parameters. Our results showed no drop in either allelic richness or expected heterozygosity over all Argentinean populations. However, a clear drop in genetic diversity was observed in two out of three location-specific time series. This loss of diversity will have negative impacts on population survival, especially over longer periods of time. Furthermore, the use and release of mass-reared specimens of B. pauloensis, which may be inbred and specifically selected for certain commercial but non-adaptive traits, could further diminish the genetic pool. Thus, our result implies the urgent need for regional conservation policies of B. pauloensis in South Brazil and North Argentina.